2015
DOI: 10.1080/00423114.2015.1064972
|View full text |Cite
|
Sign up to set email alerts
|

Rear wheel torque vectoring model predictive control with velocity regulation for electric vehicles

Abstract: In this paper we propose a constrained optimal control architecture for combined velocity, yaw and sideslip regulation for stabilisation of the vehicle near the limit of lateral acceleration using the rear axle electric torque vectoring configuration of an electric vehicle. A nonlinear vehicle and tyre model are used to find reference steady-state cornering conditions and design two model predictive control (MPC) strategies of different levels of fidelity: one that uses a linearised version of the full vehicle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…For a minimum-time cornering problem, Berntorp et al [20] showed the influence of the tire and chassis models on the computational complexity and performance of an NMPC, without providing a general conclusion. Siampis et al [21] demonstrated that the wheel dynamics do not bring a significant performance enhancement and increase complexity.…”
Section: Introductionmentioning
confidence: 99%
“…For a minimum-time cornering problem, Berntorp et al [20] showed the influence of the tire and chassis models on the computational complexity and performance of an NMPC, without providing a general conclusion. Siampis et al [21] demonstrated that the wheel dynamics do not bring a significant performance enhancement and increase complexity.…”
Section: Introductionmentioning
confidence: 99%
“…But if the target torque is constrained by the motor limit, the desired velocity and yaw motion requested by the driver may not be satisfied. By considering the longitudinal slip and motor torque constraint, MPC was utilized for the rear wheel torque vectoring, 19 but this study is based on the assumption that front-rear brake distribution is fixed.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy logic control (FLC) was used in [16,17], introducing a set of logic rules that formulate the control law and thus avoiding the complexity of dealing with nonlinear model. Successive linearization was used by [18] to linearize the model around current state and by [19] to linearize the model around current equilibrium point, both applying model predictive control (MPC) methods. A very popular approach for dealing with nonlinearity is gain-scheduling.…”
Section: Introductionmentioning
confidence: 99%